Effects of plasma surface Ta alloying on the tribology behavior of γ-TiAl - Wei D.-B.; Zhou X.; Li F.-K.; Li M.-F.; Li S.-Q.; Zhang P.-Z. (Journal of Mining and Metallurgy. Section B: Metallurgy)
To improve the wear resistance of γ-TiAl alloy, Ta alloy layer was prepared on surface by double glow plasma surface alloying technique. The tribology behavior of Ta alloy layer against Si3N4 at 25℃, 350℃ and 500℃ were comparatively studied. The results showed that Ta alloy layer comprised a deposition layer and a diffusion layer. The deposition layer played a role in protection as a soft film. With the increase of temperature, the wear mechanism of γ-TiAl changed from abrasive wear to coexistence of abrasive wear and oxidation wear. Ta alloy layer’s wear mechanism changed from adhesive wear to coexistence of adhesive wear and oxidation wear. Surface Ta alloying process significantly reduced the wear volume, the specific wear rate and the friction coefficient of γ-TiAl and improved the wear resistance properties of γ-TiAl.